OPTIMALISASI STRATEGI PEMELIHARAAN PREVENTIF UNTUK ALAT KESEHATAN DENGAN KAJIAN SISTEMATIS DARI PENDEKATAN UTAMA DAN APLIKASINYA - Kurniadi, Irwin; Gani, Ascobat (LPPM Universitas Awal Bros, 2025)
Preventive Maintenance (PM) is crucial for ensuring the reliability, safety and longevity of medical equipment in healthcare settings. This review evaluates key PM strategies emphasizing their applicability to resource-constrained hospitals. A systematic review was conducted, analyzing 19 articles selected from 37 screened, focusing on standardization, predictive maintenance, criticality-based prioritization, lifecycle management and data-driven approaches. Advantages, limitations and contextual relevance were concluded. Five main approaches were identified, standardization improves operational consistency and efficiency, while predictive maintenance enhances diagnostic accuracy and reduces downtime. Criticality-based prioritization optimizes resource allocation for high-risk devices and lifecycle management ensures sustainable use of high-value equipment. Data-driven strategies provide decision-making support but require significant technological investment. Combining standardization, criticality-based prioritization and basic predictive techniques is ideal for small and medium-sized hospitals. Larger hospitals can benefit from integrating lifecycle management and advanced data systems. A phased, flexible implementation ensures the reliability of medical equipment and the safety of patients.